2008
DOI: 10.1002/mds.22328
|View full text |Cite
|
Sign up to set email alerts
|

Pisa syndrome and Parkinsonism secondary to valproic acid in Huntington's disease

Abstract: et al. 1 reported postural tremor in one patient with polycythaemia vera which was tentatively attributed to manganese deposits in the basal ganglia and improved after therapy with a chelating agent. Herein we report a patient with polycythaemia vera who developed persistent parkinsonism and in whom MRI showed features consistent with manganism.In 1998 a 47-year-old man employee began to complain of headache and arterial hypertension that led to the diagnosis of polycythaemia vera, which were treated with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Another case study reported that VPA treatment caused a state of tolerance, however this was found in only one late-stage HD patient 168 . While VPA is generally a safe drug 169 , it is a known teratogen in both rodents 170 and humans 171 , and it should be noted that one case study reported that a single HD patient developed Pisa syndrome, an incredibly rare but dangerous neurological side effect 172 , after VPA treatment.…”
Section: Clinical Trials Of Lithium and Vpa In Hdmentioning
confidence: 99%
“…Another case study reported that VPA treatment caused a state of tolerance, however this was found in only one late-stage HD patient 168 . While VPA is generally a safe drug 169 , it is a known teratogen in both rodents 170 and humans 171 , and it should be noted that one case study reported that a single HD patient developed Pisa syndrome, an incredibly rare but dangerous neurological side effect 172 , after VPA treatment.…”
Section: Clinical Trials Of Lithium and Vpa In Hdmentioning
confidence: 99%
“…It must be noted that there has also been one report linking valproic acid treatment with the development of Pisa syndrome in a patient with HD (Salazar et al 2008). …”
Section: Hdacs Er Stress and Pro-inflammatory Pathways In Hdmentioning
confidence: 99%
“…Furthermore, a combined treatment of lithium (induces autophagy and downregulates HDAC1) and VPA produced several beneficial effects and prolonged median survival in HD transgenic mice [ 230 ]. In HD patients, valproic acid is discussed to have beneficial effects on psychiatric symptoms [ 231 ] but was also shown to have side effects like developing Parkinson's syndrome with an axial dystonia [ 232 ]. The HDAC inhibitor sodium butyrate was shown to delay the onset, ameliorate the neurological phenotype, improve the survival in SCA 3 transgenic mice, and improve the survival of neurons in an ataxin-7 cell model [ 55 , 233 ].…”
Section: Clearance Mechanismsmentioning
confidence: 99%